Ecology of seed germination of Pinus sylvestris L. at its southern, Mediterranean ditribution range - Castro, J.=700 1 Zamora, R.; Hodar, J.A.; Gomez, J.M.
(Es, En)
ilus., 49 ref.
Keywords: PINUS SYLVESTRIS; ECOLOGIA; GERMINACION; SEMILLAS; ESPAÑA; FACTORES BIOLOGICOS; FACTORES ABIOTICOS